2023
DOI: 10.3847/1538-4365/acbfa7
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Catalog of Early-type Dwarf Galaxies in the Local Universe: Morphology and Environment

Abstract: We present an extensive catalog of 5405 early-type dwarf (dE) galaxies located in the various environments, i.e., clusters, groups, and fields, of the local universe (z < 0.01). The dEs are selected through visual inspection of the Legacy survey’s g–r–z combined tricolor images. The inspected area, covering a total sky area of 7643 deg2, encompasses two local clusters (Virgo and Fornax), 265 groups, and the regions around 586 field galaxies of M K &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…We obtained preprocessed CFHT images that had undergone bias subtraction, flat-fielding, and flux calibration by the MegaCam pipeline system, ELIXIR. To further remove the sky background, we followed a method described in Paudel et al (2023), in which we generated a background map by masking out identified sources in the image using Source Extractor (Bertin & Arnouts 1996) maps. The segmentation images were then filled with median values from surrounding pixels to eliminate light contributions from stars and background galaxies.…”
Section: Visible-light Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained preprocessed CFHT images that had undergone bias subtraction, flat-fielding, and flux calibration by the MegaCam pipeline system, ELIXIR. To further remove the sky background, we followed a method described in Paudel et al (2023), in which we generated a background map by masking out identified sources in the image using Source Extractor (Bertin & Arnouts 1996) maps. The segmentation images were then filled with median values from surrounding pixels to eliminate light contributions from stars and background galaxies.…”
Section: Visible-light Observationsmentioning
confidence: 99%
“…We found an ideal target to test SED fitting in the ultralow surface brightness regime in Canada-France-Hawaii Telescope (CFHT) images as a side product of a search for nearby interacting dwarf galaxies (Paudel et al 2023) in the Sloan Digital Sky Survey and Legacy Surveys (Dey et al 2019). This is a rare ringlike tidal stellar stream (originally cataloged and classified as a polar ring galaxy by Moiseev et al 2011) around the edge-on galaxy SPRC047 (R.A. = 13 h 59 m 41 s , decl.…”
Section: Introductionmentioning
confidence: 99%
“…We also performed surface photometry on the optical images of LEDA 1915372. We utilized the legacy r-band images and subtracted the sky backgrounds using the same method described in Paudel et al (2023). To extract the galaxy's major-axis light profile, we employed the IRAF ellipse task, following the manual masking of any non-related background and foreground objects.…”
Section: Analysis Of Archival Datamentioning
confidence: 99%